Phase control of attosecond pulses in a train. (16th January 2018) - Guo, Chen; Harth, Anne; Carlström, Stefanos; Cheng, Yu-Chen; Mikaelsson, Sara; Mårsell, Erik; Heyl, Christoph; Miranda, Miguel; Gisselbrecht, Mathieu; Gaarde, Mette B; Schafer, Kenneth J; Mikkelsen, Anders; et al.
Abstract: Ultrafast processes in matter can be captured and even controlled by using sequences of few-cycle optical pulses, which need to be well characterized, both in amplitude and phase. The same degree of control has not yet been achieved for few-cycle extreme ultraviolet pulses generated by high-order harmonic generation (HHG) in gases, with duration in the attosecond range. Here, we show that by varying the spectral phase and carrier-envelope phase (CEP) of a high-repetition rate laser, using dispersion in glass, we achieve a high degree of control of the relative phase and CEP between consecutive attosecond pulses. The experimental results are supported by a detailed theoretical analysis based upon the semi-classical three-step model for HHG.